k-space imaging of the eigenmodes of sharp gold tapers for scanning near-field optical microscopy - Esmann, Martin; Becker, Simon F.; da Cunha, Bernard B.; Brauer, Jens H.; Vogelgesang, Ralf; Groß, Petra; Lienau, Christoph (Beilstein Journal of Nanotechnology, 2013)
We investigate the radiation patterns of sharp conical gold tapers, which were designed as adiabatic nanofocusing probes for scanning near-field optical microscopy (SNOM). Field calculations show that only the lowest order eigenmode of such a taper can reach the very apex and thus induce the generation of strongly enhanced near-field signals. Higher-order modes are coupled into the far field at finite distances from the apex. Here, we demonstrate experimentally how to distinguish and separate between the lowest and higher-order eigenmodes of such a metallic taper by filtering in the spatial frequency domain. Our approach has the potential to considerably improve the signal-to-background ratio in spectroscopic experiments at the nanoscale.
Keywords: adiabatic nanofocusing; Fourier optics; metallic wire modes; plasmonics; scanning near-field optical microscopy (SNOM)